2014
DOI: 10.1017/s136898001400010x
|View full text |Cite
|
Sign up to set email alerts
|

Meal pattern among Norwegian primary-school children and longitudinal associations between meal skipping and weight status

Abstract: Objective: To investigate meal pattern longitudinally and explore whether meal skipping was associated with overweight among Norwegian children and adolescents. Design: Longitudinal study. Children's meal frequencies were reported by their parents using a retrospective FFQ. Weight and height were measured by public health nurses. Descriptive data comparing 4th and 7th grade were analysed by paired-sample t tests for continuous variables and x 2 tests for categorical variables. Odds ratio estimates, including c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 33 publications
3
29
1
Order By: Relevance
“…In the literature, the association between the sociodemographics of mothers and children and the latter's breakfast‐skipping behavior is inconsistent. A small number of studies have found no difference between male and female children in this regard (Albashtawy, ; Ostachowska‐Gasior, Piwowar, Kwiatkowski, Kasperczyk, & Skop‐Lewandowska, ; Stea et al., ), which is consistent with our findings. On the other hand, some studies have highlighted gender differences (Veghari & Mansourian, ; Vereecken et al., ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the literature, the association between the sociodemographics of mothers and children and the latter's breakfast‐skipping behavior is inconsistent. A small number of studies have found no difference between male and female children in this regard (Albashtawy, ; Ostachowska‐Gasior, Piwowar, Kwiatkowski, Kasperczyk, & Skop‐Lewandowska, ; Stea et al., ), which is consistent with our findings. On the other hand, some studies have highlighted gender differences (Veghari & Mansourian, ; Vereecken et al., ).…”
Section: Discussionsupporting
confidence: 92%
“…Several reports also show that the prevalence of skipping breakfast increases with age, from early childhood through adolescence (Albashtawy, ; Smith et al., ; Stea, Vik, Bere, Svendsen, & Oellingrath, ). This finding supports the premise that early introduction of health‐promoting nutritional interventions would encourage regular breakfast consumption among children.…”
Section: Introductionmentioning
confidence: 98%
“…A cross‐sectional study considering breakfast consumption as an effect‐modifier of the relationship between eating frequency and obesity among 10‐ to 12‐year‐old boys found that, among children consuming more than three meals per day, the protective effect only held among breakfast consumers . Subsequent longitudinal studies add support to these findings .…”
Section: Discussionmentioning
confidence: 94%
“…It may be possible that the type, quantity, and/or quality of breakfast eaten at home, by those who were obese in our study, are poor choices. Research evidence examining the association between skipping meals and children's weight is limited [47,48], and, therefore, restricts our comparative analysis. However, our data showed no significant differences or association between skipping lunch and dinner, and weight status, as per a previous smaller Finnish study of 9 to 11 year old children [48].…”
Section: Discussionmentioning
confidence: 99%